Efforts to Improve the Learning Outcomes of Students of Class VII MTs Negeri 2 Rantau Utara On Material Creative Writing Poetry Through a Strategy of Cooperative Learning Type of Jig-Saw - Amron Zarkasih Ritonga (CV. AFDIFAL MAJU BERKAH, 2022)
This research is classroom action research, which aims to improve student learning outcomes on the material of creative writing poetry through a strategy of cooperative learning type of jig-saw. The research instrument used was a test of learning outcomes essay form as much as 3 grains of matter to the cycle I and 3 grains of matter to the second cycle as well as the observation sheet/studied those daycare centers on the activities of the learning process. Instrument observation sheet is used to measure the learning process while the test is used to measure the learning outcomes. To the results of the study to solve the problems of creative writing poems with the standard indicators of minimum completeness individuals of ≥ 75 and in classical ≥ 85% meet the standard of completeness. The subject of this research is the students of class VII-2 SMP Negeri 2 Rantau Utara, as many as 38 people. The results of the study concluded that the process of learning the subject matter of creative writing poem by using the strategy of cooperative learning type of jig-saw can : 1) Improve the Response and Enthusiasm to better master the learning materials on the subject matter of these. 2) Support the creation of a condition of active learning, creative and fun (CTL). 3) Improve student learning outcomes.